The Implementation of Community Based Tourism Concept In the Management of Natural Tourism in Kampoeng Karts Rammang-Rammang Maros Regency - Syarifuddin Syarifuddin (UNM Geographic Journal, 2018)
The objectives of this research were to found out (1) the implementation of the principle of CBT in the Rammang-Rammang Kampoeng Karts Nature Tourism; (2) the suitability between management and the criteria for implementing CBT (3) its development efforts, and (4) its integration into Geography learning. This research applied a qualitative descriptive approach. It was a case study on the management of Rammang-Rammang Kampoeng Karts Nature Tourism.. Data collection techniques through interview, observation and documentation. The results showed that (1) Kampoeng Karts Nature Tourism Rammang-Rammang has implemented the principle of CBT in economic, social, cultural, political and environmental aspects. But it less in the cultural and political aspects, the local society were impressed not welcome the visitor. Cultural exchange did not appear because there were not cultural or artistic performances. POKDARWIS focuses on community assistance; (2) its management had been compatible with the CBT criteria, namely obtaining community support, economic benefits and tourism to protect the culture and environment; (3) the development of infrastructure quantity and service quality. But still lack of the availability of clean water, resting places, cafes and inns; (4) it could be integrated in Geography learning to study geosphere objects as learning media and observation locations.Tujuan penelitian ini untuk mengetahui (1) penerapan prinsip CBT di Wisata Alam Kampoeng Karts Rammang-Rammang; (2) kesesuaian antara pengelolaannya dengan  kriteria penerapan CBT (3) usaha pengembangannya, dan (4) pengintegrasiannya dalam pembelajaran Geografi. Penelitian ini menggunakan pendekatan dekriptif kualitatif. Jenis penelitian adalah studi kasus pada pengelolaan Wisata Alam Kampoeng Karts Rammang-Rammang. Dengan teknik pengambilan data melalui wawancara, observasi dan dokumentasi. Hasil penelitian menunjukkan bahwa (1) Wisata Alam Kampoeng Karts Rammang-Rammang telah menerapkan prinsip CBT dalam aspek ekonomi, sosial, budaya, politik, dan lingkungan. Pada indikator penghargaan terhadap budaya yang berbeda belum maksimal disebabkan masyarakat setempat belum terbuka terhadap pengunjung dan belum adanya  atraksi budaya. Indikator meningkatkan kekuasaan belum terwujud disebabkan POKDARWIS fokus pada pendampingan masyarakat; (2) pengelolaan Wisata Alam Kampoeng Karts Rammang-Rammang sesuai dengan kriteria CBT, yaitu mendapat dukungan masyarakat, bermanfaat ekonomis dan kepariwisataan melindungi budaya dan lingkungan; (3) sudah menunjukkan perkembangan dari segi kuantitas sarana prasarana maupun kualitas pelayanan. Namun ketersediaan air bersih, tempat istirahat, kafe dan penginapan masih minim; (4) Wisata Alam Kampoeng Karts Rammang-Rammang dapat diintegrasikan dalam pembelajaran Geografi untuk mengkaji obyek geosfer melalui pemanfaatannya sebagai media pembelajaran dan sebagai lokasi observasi.